2022
DOI: 10.3390/v14071384
|View full text |Cite
|
Sign up to set email alerts
|

Disinfectants against African Swine Fever: An Updated Review

Abstract: African Swine Fever (ASF), a hemorrhagic disease with a high mortality rate in suids, is transmitted via direct and indirect contact with infectious animals and contaminated fomites, respectively. ASF reached Europe in 2014, affecting 14 of the 27 EU countries including, recently, the Italian peninsula. The fast and unprecedented spread of ASF in the EU has highlighted gaps in knowledge regarding transmission mechanisms. Fomites, such as contaminated clothing and footwear, farming tools, equipment and vehicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In summary, the recommendations that seem most feasible are related to the washing and disinfection. ASFV, as a complex enveloped virus, is susceptible to detergents such as soaps, as well as to several disinfectants and dehydration ( 34 ). However, many disinfectants are unsuitable for use in practice, because of safety issues: the cleaning staff are using disinfectants in a confined space and, therefore, any disinfectant that may cause skin or eye irritation or be suspect of carcinogenic effect is not permitted to be used in Denmark.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the recommendations that seem most feasible are related to the washing and disinfection. ASFV, as a complex enveloped virus, is susceptible to detergents such as soaps, as well as to several disinfectants and dehydration ( 34 ). However, many disinfectants are unsuitable for use in practice, because of safety issues: the cleaning staff are using disinfectants in a confined space and, therefore, any disinfectant that may cause skin or eye irritation or be suspect of carcinogenic effect is not permitted to be used in Denmark.…”
Section: Resultsmentioning
confidence: 99%
“…This rules out e.g., glutaraldehyde. Many factors need to be taken into account, when setting up a robust system, e.g., if organic material is present when disinfected, the efficiency of disinfectants like chlorine compounds and oxidizing agents will be reduced ( 34 ). The search for new, safe and more efficient disinfectants that can be applied is important.…”
Section: Resultsmentioning
confidence: 99%
“…Enveloped viruses, including ASFV, are among the least challenging pathogens for inactivation because they are susceptible to a wide range of disinfectants [ 145 ]. A number of recent studies have confirmed the efficacy of commonly used disinfectants against ASFV and provide details on concentration and contact times, as well as broadening the range to include citric and acetic acid, despite the wide pH tolerance range of ASFV [ 145 , 146 , 147 ]. Sodium hydroxide and calcium hydroxide remain disinfectants of choice in the presence of organic material [ 145 ].…”
Section: Mitigating Well-documented Risksmentioning
confidence: 99%
“…It is well known that ASF virus can be transmitted to domestic pigs and wild boar through direct and/or indirect contact with infected animals, contaminated fomites and through the ingestion of contaminated meat products (Olesen et al, 2020;Bellini et al, 2021). Th e virus is highly resistant to environmental conditions and can persist in contaminated fomites and meat products for several months, contributing to the disease spread (Mazur-Panasiuk et al, 2019; Beato et al, 2022). In many cases, the exact route of introduction into domestic pig herds cannot be determined, but most introductions are attributed to indirect virus transmission (Ståhl et al, 2019;Olesen et al, 2020).…”
Section: Afrička Kuga Svinja: Biosigurnosni Izazov Za Proizvodnju Dom...mentioning
confidence: 99%
“…Regardless of the type of production, high levels of farm biosecurity are considered the most important tools for preventing introduction of ASFV. Biosecurity measures on farms and especially at the farm entrance (thorough cleaning and disinfection and personal protective equipment) have an important role in any type of pig production (Bellini et al, 2021;Beato et al, 2022). Lamberga et al (2020) recently described an ASF outbreak at a large commercial pig farm in Latvia, where the weakest points identifi ed were the entrances of the farm.…”
Section: Biosecurity Challenge In Commercial Pig Production Sector In...mentioning
confidence: 99%